Key Factors for Defining the Conceptual Framework for Quality Assurance in E-Learning - Marwah Khaleel Farhan; Hasanien Ali Talib; Mazin S. Mohammed (Journal of Information Technology Management)
E-learning has evolved for more than a decade, and universities are gradually embracing e-learning to provide more learning experience for their learners. E-learning is the use of electronic means through which training is received and obtained. E-learning offers a wide range of advantages (time and room mobility, cost-effectiveness, etc.) and also overcomes the limitations of digital learning that have led to the widespread adoption of the institute. The poor quality of e-learning services is one of the main causes of the number of errors collected. Experts proposed performance models for e-learning systems, but most relied solely on pedagogical opinions. From a software perspective, very limited attention is paid to evaluating the performance of e-learning applications. It is therefore quite difficult to evaluate the overall performance of the e-learning scheme effectively. The aim of this study is to draw up separate stakeholders in the e-learning system by providing a roadmap to ensure the effectiveness of their e-learning facilities, particularly in emerging countries and Iraq. The higher education data system guarantees and measures the performance of its e-learning system in its own way, as there is no specific definition of the performance of the e-learning system. This work is expected to be ready to harmonize the various stakeholders to a satisfactory standard within the performance framework.